A single-center experience of central nervous system tumors in children under three years old - Wang, Junhua; Wang, Chuanwei; Huang, Zhimin; Zhang, Zhihua; Zhang, Yuqi (Frontiers in Pediatrics, 2024)
Purpose: This study aims to summarize the characteristics of children under three years old (≤3 y) with central nervous system (CNS) tumors and to investigate the factors that influence their overall survival (OS) time. Methods: We treated 171 pediatric patients (≤3 y) with CNS tumors at Yuquan Hospital of Tsinghua University from January 2016 to June 2023. Of these, 162 cases were successfully followed up. Kaplan-Meier survival analysis and Cox regression were utilized to evaluate factors potentially influencing OS of malignancies. Results: There was a male predominance among the patients. The three most common tumors were embryonal tumors, gliomas, and craniopharyngiomas. Gross total resection (GTR) was achieved in select cases. Patients with high-grade malignancies were advised to undergo chemotherapy and/or radiotherapy after surgery. Optic gliomas and diffuse midline gliomas were partially resected and treated with adjuvant treatments. The median survival time of low-grade malignant tumors was 41.5 months, while that of high-grade malignant tumors was 15 months. Kaplan-Meier survival analysis identified the factors potentially influencing OS of malignancies: extent of resection, CNS WHO grade, grade of malignancies, and Ki-67 labeling index (Ki-67 LI). Subsequent multivariate analysis highlighted the interactive factor (extent of resection × CNS WHO grade) along with Ki-67 LI, as the most significant variables. Factors such as sex, age, tumor location, and onset-to-treatment time appeared not to affect OS. Conclusions: GTR remains the cornerstone of treatment for children (≤3 y) with CNS tumors, except for optic glioma, diffuse midline glioma, and germinoma. The interactive factor (extent of resection × CNS WHO grade) and Ki-67 LI are the most significant factors affecting OS. The implementation of preoperative neoadjuvant chemotherapy and early postoperative chemotherapy may enhance prognosis.